PERINTISAN WIRAUSAHA BERBASIS PESANTREN MELALUI PELATIHAN DANPENDAMPINGAN WIRAUSAHA PADA SANTRI PP ASY-SYIFA SARUNI PANDEGLANG - Urika, Urika; Rahmiyanti, Sev; Noviani, Lona; Nurfarisyi, Muhammad Ikhsan; Umbara, Pandu Setia (Universitas Mataram, 2024)
This Community Service Program (PKM) aims to pioneer and develop pesantren-based entrepreneurs through a series of entrepreneurial training and mentoring activities aimed at students of PP Asy-Syifa, Saruni, Pandeglang. Pesantren as Islamic educational institutions have great potential in developing community-based economies, but often do not have adequate access and skills to develop independent and sustainable businesses. The implementation of this program is focused on improving the skills of students in the field of entrepreneurship through intensive training and continuous mentoring. The results of this program show an increase in entrepreneurial skills among students, the establishment of two new business units managed by the pesantren, namely hydroponic vegetable farming and fish farming, and ongoing support from mentors to ensure business sustainability. With this training and mentoring, the students of PP Asy-Syifa not only gain practical knowledge about entrepreneurship, but are also able to apply it directly in business development. This program is expected to become a model of pesantren-based entrepreneurship pioneering that can be replicated in other pesantren, thus contributing to the economic independence of pesantren and improving the welfare of pesantren communities in Pandeglang and surrounding areas.